Synthesis of nanoparticles of nickel oxide in the diffusion flame оn a collision of the jet - Lesbayev, B.T.; Auyelkhankyzy, M.; Mansurov, B.Z.; Lesbayev, A.B.; Turesheva, G.O.; Prihodko, N.G.; Mansurov, Z.A. (Recent Contributions to Physics, 2012)
The paper presents the results of the study synthesis of nanoparticles of nickel oxide. The synthesis was carried out on the surface of the nichrome wire 0.3 mm in diameter in the diffusion of propane-oxygen flame in colliding jets. With a nichrome wire in a certain area of the flame and varying the time of processing, have been synthesized nickel oxide nanoscale particles ranging in size from 70 nm to 500 nm. Studies have been conducted of the samples by scanning electron and atomic force microscopy.